Fatigue in inflammatory bowel disease and its impact on daily activities. Issue 1 (7th November 2020) - Schreiner, Philipp; Rossel, Jean‐Benoît; Biedermann, Luc; Valko, Philipp O.; Baumann, Christian R.; Greuter, Thomas; Scharl, Michael; Vavricka, Stephan R.; Pittet, Valérie; Juillerat, Pascal; Rogler, Gerhard; von Känel, Roland; et al.
Summary: Background: Fatigue is a common symptom of chronic inflammation, including inflammatory bowel disease (IBD), resulting in significant impairment in quality of life. Aims: To identify the prevalence of fatigue in a large IBD cohort compared to the general population, address risk factors, and evaluate its impact on daily life. Methods: We evaluated 1208 IBD patients from the Swiss Inflammatory Bowel Disease Cohort Study (SIBDCS) and 414 healthy controls. Significant fatigue was defined as a visual analogue scale (VAS‐F, range 0‐10) score ≥ 4. Secondary endpoints were severity of fatigue and its impact on daily activities with the Fatigue Severity Scale (FSS), with a score ≥ 4 indicative of fatigue. Demographic, IBD‐related and psychiatric symptoms were assessed with a multivariate analysis of variance (MANOVA) model optimised for prediction of VAS‐F (primary outcome) and FSS scores. Results: Overall, 672 IBD patients (55.6%) reported significant fatigue compared to 145 (35%) controls (OR 2.71; 95% CI 2.08‐3.54; P < 0.001). In IBD, fatigue also significantly affected daily activities (FSS ≥ 4; 405 (33.5%) IBD patients vs 81 (19.6%) controls, P < 0.001). In the MANOVA model, fatigue levels were associated with female gender (coefficient 0.839; 0.556 ‐ 1.123; P < 0.001), younger age at diagnosis (−0.031 per year; −0.042– −0.019; P < 0.001), shorter disease duration (−0.036 per year; −0.050– −0.022; P < 0.001), nocturnal diarrhoea (0.718; 0.295‐1.141; P = 0.001), low educational level ( P = 0.034) and symptoms of depression and anxiety. Conclusions: Fatigue is both more frequent and more severe in patients with IBD than in the general population.